Adsorption of antibiotics using carbon nanotube - Kee, Mattheus Jian Yang (2017)
Antibiotics has been used extensively during the past few decades, leading to increase in their existence in the surrounding environment and has introduced potential impacts on our health and ecology. The ability of utilising Carbon Nanotube as an adsorbent to remove these antibiotics were evaluated in this study. The antibiotics used in this study were representative Beta-Lactum antibiotics; Ampicillin Sodium Salt and Penicillin G. The removal percentage of antibiotics increases when the dosage of adsorbent increases. The Freundlich Isotherm equation which assumes a heterogenous adsorbent surface with multilayer adsorption is a better indication for the adsorption process. Furthermore, the adsorption process is better decided by pseudo second order kinetic which has a better fitting. The antibiotic removal percentage of Carbon Nanotube were found to be different from prediction. The removal percentage were lower for Carbon Nanotube when compared with Powdered Activated Carbon. This could be due to the hydrophobic nature of Carbon Nanotube which decreases total available adsorption sites.